Utilization of Banana Stem Waste Extracts Assisted by Electrode of Cu/Mg as an Environmentally Friendly Electricity Producer - Rokhim, Deni Ainur; Adid, Ahmad Wahani; Tyas, Frida Kristining; Ciptawati, Endang; Asrori, Muhammad Roy (Orbital: The Electronic Journal of Chemistry, 2022)
The high consumption of electricity from year to year and the depletion of the availability of fossil energy have triggered an increase in energy prices and scarcity of fossil resources. This problem gives a strong impetus to seek alternative energy sources that are environmentally friendly. One of the recent technologies is the Microbial Fuel Cell (MFC) on banana stem, which can convert chemical energy into electrical energy. The purpose of this study was to determine the potential of banana stem waste extract assisted by Cu/Mg electrodes as a source of electricity as well as how the manufacturing and testing methods, and the effect of variations in the volume of banana stem extracts on the performance of electrical energy. The used steps were electrode preparation and banana stem waste preparation, then incubating the banana stem waste for 7 days, assembling the construction for research on the potential of the banana stem waste as a power producer, and research with variations in the volume of the extract and testing its strength, electric current, electric voltage, and power density. Based on the research, it was found that the greater the volume of the extract of banana stem, the greater the power density, electric voltage, and also the strong electric current produced. The volume variation of 130 mL produced a voltage of 500 mVolt, a strong current of 0.86 mA, and a power density of 84 (mW/cm2). DOI: http://dx.doi.org/10.17807/orbital.v14i1.1677